Enhanced mineralization of bisphenol A by Electric Arc Furnace Slag: Catalytic Ozonation - Fasce, Laura Alejandra (2023)
The catalytic ozonation of bisphenol A (BPA) was performed using an industrial solid waste ascatalyst: electric arc furnace slag (EAFS). The characterization of the catalyst (SEM/EDS, XRD,surface area, pHPZC and Mössbauer spectroscopy) showed low surface area, alkaline nature and acomposition rich in Fe, Ca, Si, C oxides, with minor content of Mg, Mn and Al. Ozonationexperiments were carried out in a semi-batch reactor at room temperature at different initial pHconditions: from alkaline (natural pH 10.5) to acidic (controlled pH 3) aqueous media. Catalyticozonation experiments showed complete BPA removal and remarkable total organic carbonconversions (62-80%) over the broad pH range explored. The highest mineralization levels wereobtained under basic pH, which was attributed to the generation of hydroxyl radical given by thepresence of OHand precipitation reactions of intermediates promoted by Ca oxides. Under acidicconditions the presence of EAFS notoriously enhanced BPA mineralization compared to singleozonation, due to the activity of leached species. The stability of the material was tested in 4 ozonation cycles. EAFS activity was mostly sustained under acidic conditions while a reduction was observed under uncontrolled pH condition, which was associated with a marked pH decrease. However, the residual activity still allowed complete BPA degradation and high mineralization levels (> 50 %). EAFS is a low-cost material that exhibits high activity and reasonable stability in catalytic ozonation of BPA. The valorization of this waste constitutes a technological alternative that could benefit both metallurgical and water treatment plants.